PENGARUH KECERDASAN EMOSIONAL (EQ) MAHASISWA DAN METODE PENGAJARAN DOSEN TERHADAP TINGKAT PEMAHAMAN AKUNTANSI - Lutfi Baradja; Ayu Aulia Oktaviani (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
The purpose of this research was to examine the effect of students' emotional intelligence and lecturer teaching methods on accounting understanding level. This study used questionnaire techniques. The sample used was 69 respondents with a purposive sampling method. The analytical technique used in this study is multiple regression. The results shown are that emotional intelligence affects the level of accounting understanding, while the teaching method of lecturers has no effect on the level of accounting understanding. Through the results of this research, it is expected that universities can strive to increase the students emotional intelligence as a measure of accounting understanding level because it can improve the quality of graduates. This research is important in education, especially universities which certainly wants the highest quality graduates, and for students to improve material understanding.